(3PcQ CSeGA GdJGHYjf hef HYOge eef UMJ QhGjJg YfO GdHNGQi heSdes - (3Ydj Hf YeQ Hf CMeO Hf egOj, CHh GdMSf GdqOGQbWfqj GdTGaYqj,J (B385 (3g` s
(3ChdgG (B:s
(3PcQ CSeGA ef GTJed Ydjge cJGH eMeO Hf ESeGYjd GdHNGQi s
(3BNQgG (B:s
(3BNQ GdcJGH hGdMeO ddg QH GdYGdejf s
(3fSNI fbdJ ef NW GdOGQbWfi Yf fSNI GdMejOis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B314 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B157s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B137 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI chHQjdi (B(40/4) s
Keywords: (3GdJGQjNs